2022
DOI: 10.1016/j.molp.2021.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequences of five Sitopsis species of Aegilops and the origin of polyploid wheat B subgenome

Abstract: Common wheat (Triticum aestivum, BBAADD) is a major staple food crop worldwide. The diploid progenitors of the A and D subgenomes have been unequivocally identified; that of B, however, remains ambiguous and controversial but is suspected to be related to species of Aegilops, section Sitopsis. Here, we report the assembly of chromosome-level genome sequences of all five Sitopsis species, namely Aegilops bicornis, Ae. longissima, Ae. searsii, Ae. sharonensis, and Ae. speltoides, as well as the partial assembly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 98 publications
9
121
4
Order By: Relevance
“…Preferential transmission of chromosome 2S of Ae. speltoides , proposed to be more closely related to the T. timopheevii G genome than to the B genome of wheat (Li et al, 2022; Rodriguez et al, 2000a), is well documented (King et al, 2018; Tsujimoto and Tsunewaki 1988) although the gene causing the preferential transmission in T. timopheevii appears to be weaker than the gene for preferential transmission in Ae. speltoides .…”
Section: Discussionmentioning
confidence: 99%
“…Preferential transmission of chromosome 2S of Ae. speltoides , proposed to be more closely related to the T. timopheevii G genome than to the B genome of wheat (Li et al, 2022; Rodriguez et al, 2000a), is well documented (King et al, 2018; Tsujimoto and Tsunewaki 1988) although the gene causing the preferential transmission in T. timopheevii appears to be weaker than the gene for preferential transmission in Ae. speltoides .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research indicated that Ae. speltoides was not the direct progenitor of the B genome [45]. The comparison of genome sequences of five Aegilops Sitopsis species showed that Ae.…”
Section: Origin Domestication and Evolution Of Tetraploid Wheat 21 Or...mentioning
confidence: 99%
“…The comparison of genome sequences of five Aegilops Sitopsis species showed that Ae. speltoides and the B-subgenome diverged about 4.49 million years BP, which was much earlier than the speciation of tetraploid emmer wheat [45]. The long evolution history after tetraploid wheat generation may result in the high divergence of B genomes between hexaploid and diploid donors, making it difficult to deduce the precise donor/s [46,47].…”
Section: Origin Domestication and Evolution Of Tetraploid Wheat 21 Or...mentioning
confidence: 99%
“…Wheat ( Triticum aestivum ) is an allohexaploid crop containing three genomes (2n = 6× = 42, AABBDD). The tetraploid T. turgidum (2n = 4× = 28, AABB) was first originated from the progeny of the polyploidization of T. urartu (donor of A genome) and an unknown diploid species of the Sitopsis (donor of B genome) [ 1 ]. Then, the hexaploid wheat was generated from the allopolyploid between T. turdidum and Aegilops tauschii (donor of D genome) about 10,000 years ago [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tetraploid T. turgidum (2n = 4× = 28, AABB) was first originated from the progeny of the polyploidization of T. urartu (donor of A genome) and an unknown diploid species of the Sitopsis (donor of B genome) [ 1 ]. Then, the hexaploid wheat was generated from the allopolyploid between T. turdidum and Aegilops tauschii (donor of D genome) about 10,000 years ago [ 1 , 2 ]. Numerous reciprocal or Robertsonian translocations have been detected in global accessions of polyploidy wheat species [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%